Oral steroids alone or followed by intranasal steroids versus watchful waiting in the management of otitis media with effusion. Issue 10 (15th August 2017) - Hussein, A; Fathy, H; Amin, S M; Elsisy, N
Abstract: Objective: To evaluate the effects of oral steroids alone or followed by intranasal steroids versus watchful waiting on the resolution of otitis media with effusion in children aged 2–11 years. Methods: A total of 290 children with bilateral otitis media with effusion were assigned to 3 groups: group A was treated with oral steroids followed by intranasal steroids, group B was treated with oral steroids alone and group C was managed with watchful waiting. Patients were evaluated with audiometry and tympanometry. Results: The complete resolution rates of otitis media with effusion were higher in groups A and B than in group C at six weeks. There were no significant differences in otitis media with effusion resolution rates between the groups at three, six and nine months. Conclusion: Oral steroids lead only to a quick resolution of otitis media with effusion, with no long-term benefits. There was no benefit of using intranasal steroids in the management of otitis media with effusion.